A practical method to identify displaced and split stratospheric polar vortex events. Issue 19 (1st October 2013) - Seviour, William J. M.; Mitchell, Daniel M.; Gray, Lesley J.
<x xml:space="preserve">Abstract</x> [1] Extreme variability of the stratospheric polar vortex during winter can manifest as a displaced vortex event or a split vortex event. The influence of this vortex disruption can extend downwards and affect surface weather patterns. In particular, vortex splitting events have been associated with a negative Arctic Oscillation pattern. An assessment of the impacts of climate change on the polar vortex is therefore important, and more climate models now include a well‒resolved stratosphere. To aid this analysis, we introduce a practical threshold‒based method to distinguish between displaced and split vortex events. It requires only geopotential height at 10 hPa to measure the geometry of the vortex using two‒dimensional moment diagnostics. It captures extremes of vortex variability at least, as well as previous methods when applied to reanalysis data, and has the advantage of being easily employed to analyze climate model simulations.